Romanian Orthodox elementary denominational schools in Transylvania (1868–1921) - Brusanowski, Paul (HTS teologiese studies, 2023)
This article presents the development of elementary schools supported by the Orthodox Church in Transylvania between 1868 and 1921. Until 1918, Transylvania belonged to Hungary. In 1918, it was united with the Kingdom of Romania. As Hungary was a particularly complex state in ethnic and confessional terms before 1918, the school system developed under the coordination and financing of the churches. The government intended to gradually replace them with schools run by communities or state. It was not until the end of the 19th century that radical measures were taken. The situation was fully resolved just after the unification of Transylvania with Romania when Romanian Orthodox denominational schools were nationalised and transformed into state schools.Contribution: Although summary works on the history of education in Romania or various research on the history of schools at the local level have appeared in Romanian, the impact of governmental and legislative decisions in Hungary on Orthodox confessional education in Transylvania has not been analysed. In German, the historian Joachim von Puttkamer has dealt with this perspective but especially concerning the schools in the Slovak areas of Greater Hungary. This PhD thesis of the author, P Brusanowski, was the first approach in this direction regarding the Romanians in Transylvania. The article presents for the first time in English a short analysis of the relationship of the Orthodox Church authorities in Transylvania to the educational policy decisions of the central authorities in Budapest. The parallel use of the reports of the Ministry of Education to the Hungarian Parliament, and the reports of the school councils of the executive body of the Romanian Orthodox Church in Transylvania to the ecclesiastical legislative forum, is an important part of this article.